Estudo comparativo da maturação óssea das vértebras cervicais, por meio de radiografias cefalométricas laterais, com as más-oclusões classes I e II de angle - Armond, Mônica Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The estimation of puberal growth of the cervical vertebrae, examined through side cephalometric radiographs, has been more an more studied and used by orthodontists an facial orthopedists due to its reliability an simplicity, besides minimizing the ionizing exposure to the patients. The aim in this research has been to compare the phases oh the bone maturation of cervical vertebrae, according to the Hassel & Farman method26(1995) with the malocclusion Classes I and II of Angle5(1899). The radiographs examination of the cervical vertebrae has been carried out, through cephalometric radiographies, in lateral norm, and the malocclusions through studying models in plaster. For this research 194 brazilian patients who had never undergone a previous orthodontic/facial orfhopedic treatment have been chosen. From this group 90 were boys and 104 were girls, all of them between ten and 14 years old. After statisfical analysis, the results allowed the conclusion that there has not been a significant statistic association between the bone maturation phases of the cervical vertebrae with the malocclusion Classes I and II of Angle, and both the examination of the phases of the cervical vertebrae and the evaluation of the dental malocclusions of Angle should be interpreted in a single and independent way

A estimativa de crescimento puberal pelas vértebras cervicais, inspecionadas por meio de radiografias cefalométricas laterais, tem sido cada vez mais estudada e utilizada pelo ortodontista/ortopedista facial em função de sua facilidade e confiabilidade, além de minimizar exposição ionizante aos pacientes. O propósito nesta pesquisa foi comparar as fases de maturação óssea das vértebras cervicais, de acordo com o método de Hassel & Fannan26 {1995) com as más-oclusões Classes I e II de Angle5(1899). A inspeção das vértebras cervicais foi realizada, por meio de radiografias cefalométricas em norma lateral, e as más-oclusões através de modelos de estudo em gesso. Foram selecionados 194 pacientes brasileiros sem tratamento ortodôntico/ortopédico facial prévio, sendo 90 meninos e 104 meninas, na faixa etária dos dez aos 14 anos de idade. Após análise estatística, os resultados permitiram concluir que não houve correlação estatística significante entre as fases de maturação óssea das vértebras cervicais com as más-oclusões Classes I e II de Angle e que tanto a inspeção das fases das vértebras cervicais quanto a avaliação das más-oclusões dentárias de Angle devem ser interpretados de forma individual e independente
Keywords: Cefalometria; Ossos - Crescimento; Radiologia; Malocclusion